Coaches' Implementation of the USA Football "Heads Up Football" Educational Program. Issue 2 (March 2018) - Kerr, Zachary Y.; Kroshus, Emily; Lee, Joseph G. L.; Yeargin, Susan W.; Dompier, Thomas P.
An integral part of the Heads Up Football (HUF) educational program is the Player Safety Coach (PSC), who is responsible for teaching other coaches within a youth football league about safer blocking/tackling and injury prevention. This study examines the association between youth football coaches' interactions with the PSC (i.e., attending the PSC clinic at the beginning of the season and seeing the PSC on-field during practices) and their subsequent implementation of the HUF educational program. Data were collected via online questionnaire completed by 1, 316 youth football coaches from HUF leagues. Data were analyzed with frequencies and logistic regression. Nearly half of coaches (44.8%) did not attend the PSC clinic; 25.9% reported not seeing their league's PSC on the field on a regular basis. The lack of PSC on-site presence was significantly associated with worse implementation for "concussion recognition and response, " "heat preparedness and hydration, " and "sudden cardiac event preparedness." PSC clinic attendance was not associated with implementation. Opportunities exist for improvement in the HUF educational program as there appears to be inconsistent implementation. Further research is warranted to understand how to optimize the role of the PSC in the youth sports context.